Serum Calcification Propensity and the Risk of Cardiovascular and All-Cause Mortality in the General Population: The PREVEND Study. Issue 8 (August 2020) - Eelderink, Coby; te Velde-Keyzer, Charlotte A.; Frenay, Anne-Roos S.; Vermeulen, Emma A.; Bachtler, Matthias; Aghagolzadeh, Parisa; van Dijk, Peter R.; Gansevoort, Ronald T.; Vervloet, Marc G.; Hillebrands, Jan-Luuk; Bakker, Stephan J.L.; van Goor, Harry; et al.
Abstract : Objective: Vascular calcification contributes to the cause of cardiovascular disease. The calciprotein particle maturation time (T50 ) in serum, a measure of calcification propensity, has been linked with adverse outcomes in patients with chronic kidney disease, but its role in the general population is unclear. We investigated whether serum T50 is associated with cardiovascular mortality in a large general population-based cohort. Approach and Results: The relationship between serum T50 and cardiovascular mortality was studied in 6231 participants of the PREVEND (Prevention of Renal and Vascular End-Stage Disease) cohort. All-cause mortality was the secondary outcome. Mean (±SD) age was 53±12 years, 50% were male, and mean serum T50 was 329±58 minutes. A shorter serum T50 is indicative of a higher calcification propensity. Serum T50 was inversely associated with circulating phosphate, age, estimated glomerular filtration rate, and alcohol consumption, whereas plasma magnesium was positively associated with serum T50 ( P <0.001, total multivariable model R 2 =0.281). During median (interquartile range) follow-up for 8.3 (7.8–8.9) years, 364 patients died (5.8%), of whom 95 (26.1%) died from a cardiovascular cause. In multivariable Cox proportional hazard models, each 60 minutes decrease in serum T50 was independently associated with a higher risk of cardiovascular mortality (fully adjusted hazard ratio [95% CI], 1.22 [1.04–1.36], P =0.021). This association was modified by diabetes mellitus; stratified analysis indicated a more pronounced association in individuals with diabetes mellitus. Conclusions: Serum T50 is independently associated with an increased risk of cardiovascular mortality in the general population and thus may be an early and potentially modifiable risk marker for cardiovascular mortality. Abstract : Supplemental Digital Content is available in the text.